EVALUATION OF SHIP ROUND TRIP TIME TO IMPROVE PERFORMANCE AT BAKAUHENI CROSSING PORT OF LAMPUNG PROVINCE - Noor Sulistiyono; Monica Amanda; Afra Salsabila (IWTJ : International Water Transport Journal, 2021)
Bakauheni Crossing Port is a port that connects the island of Sumatra and Java. Bakauheni Crossing Port has 73 ships in operation, with 3 docking vessels and 70 ships ready for operation. Bakauheni Crossing Port has also set a schedule made every month by the Land Transportation Management Agency region VI Bengkulu and Lampung. However, there is a discrepancy between the arrival and departure time of the ship with the schedule that has been made. This is evidenced by the number of News Delay Events found. This research is a combined research of quantitative and qualitative methods incorporated into one and is often referred to as mixed methods. Combined research is a stage of data collection, data analysis, with a combination of methods sequentially, namely quantitative and qualitative methods or vice versa. In the making of this study, researchers collect the results of interviews, document analysis, discussions to observation transkip and measuring instruments or research instruments, data analysis is quantitative or statistical with the aim of testing hypotheses that have been made. It can also attach qualitative and quantitative data in the form of photos or video recordings, survey methods and experimental methods. The data used is primary and secondary data to be analyzed. Based on the results of the analysis of problems in scheduling departures and arrivals at the Bakauheni Crossing Port, there were still delays that caused hampering the ship's performance afterwards. Therefore, it is necessary to further analyze Round Trip Time (RTT) to improve performance at Bakauheni Crossing Port so that the schedule of departure and arrival of ships that have been made by the Land Transportation Management Hall VI Bengkulu and Lampung can be in accordance with The Minister of Transportation Regulation No. 20 of 2018 on Organization and Work Procedures in the Land Transportation Management Hall.